Litpop : writing and popular music - Carroll, Rachel; Hansen, Adam (Ashgate popular and folk music series., 2014)
Bringing together exciting new interdisciplinary work from emerging and established scholars in the UK and beyond, Litpop addresses the question: how has writing past and present been influenced by popular music, and vice versa? Contributions explore how various forms of writing have had a crucial role to play in making popular music what it is, and how popular music informs 'literary' writing in diverse ways. The collection features musicologists, literary critics, experts in cultural studies, and creative writers.